1998
DOI: 10.1093/carcin/19.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Lack of promoting effects of the electromagnetic near-field used for cellular phones (929.2 MHz) on rat liver carcinogenesis in a medium- term liver bioassay

Abstract: The possible cancer promotion potential of local exposure to a pulse modulated 929.2 MHz electromagnetic near-field on chemically-initiated rat liver carcinogenesis was investigated employing a medium-term bioassay. A 929.2-MHz electromagnetic near-field of time division multiple access (TDMA) signal for PDC (Personal Digital Cellular, Japanese cellular telephone standard) system was directed to rats through a quarter-wavelength monopole antenna. Maximum local specific absorption rates (SARs) on temporal avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 32 publications
0
20
1
Order By: Relevance
“…Comparison of numbers and areas of GST-P-positive liver foci in rats exposed to 929. using the same rat liver medium-term bioassay did not demonstrate any enhancement of preneoplastic lesion development. 16) In the present study, an EMF of 1.439 GHz pulse modulated microwaves also did not enhance the appearance of GST-P-positive liver foci, the numbers in the EMF-exposed group, in fact, being significantly lower than in the sham-exposed group. These data clearly showed that exposure to an EMF of either 929.2 MHz or 1.439 GHz as used in cellular phones in Japan does not have any promoting potential on rat liver preneoplastic lesion development.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…Comparison of numbers and areas of GST-P-positive liver foci in rats exposed to 929. using the same rat liver medium-term bioassay did not demonstrate any enhancement of preneoplastic lesion development. 16) In the present study, an EMF of 1.439 GHz pulse modulated microwaves also did not enhance the appearance of GST-P-positive liver foci, the numbers in the EMF-exposed group, in fact, being significantly lower than in the sham-exposed group. These data clearly showed that exposure to an EMF of either 929.2 MHz or 1.439 GHz as used in cellular phones in Japan does not have any promoting potential on rat liver preneoplastic lesion development.…”
Section: Discussioncontrasting
confidence: 53%
“…In our previous experiment, 16) corticosterone and ACTH levels in serum were significantly increased in both EMFexposed and sham-exposed groups. The reason for this was speculated to be the elevation of body temperature of the rats in the exposure box.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Survival analysis also showed no significant difference in cumulative percentage survival between them. Imaida et al [1998a] investigated whether exposure of F344A rats to near field, TDMA modulated 929.2 MHz RFEMF at 50 pulses/s, 0.33 duty cycle [the Japanese standard signal for Personal Digital Cellular (PDC) telephones] would promote liver cancer initiated by the carcinogen diethylnitrosamine. Each rat was exposed for 90 min/day, 5 days/week for 6 weeks.…”
Section: Mammals Exposed In Vivomentioning
confidence: 99%